Notes on Malesherbia (Passifloraceae) in Peru: a new species from southern Peru, a new record and a first report on interspecific hybridization in Malesherbia - Weigend, Maximilian; Jossberger, Thomas; Beltrán, Hamilton (Phytotaxa, 2015)
Malesherbia fatimae is described as a new species from the Province Condesuyos, Department of Arequipa, Peru. The new species is clearly differentiated from all know species of the genus by forming a strictly erect, laxly branched shrub with densely tomentose indument and from the perennial Peruvian members by an absence of the glandular trichomes. No clear affinities to know species present themselves, but the new species evidently belongs to Malesherbia sect. Malesherbia. At the type locality a putative hybrid with the morphologically highly divergent Malesherbia tenuifolia was observed, showing morphologically intermediate characters between M. fatimae and M. tenuifolia. Malesherbia tenuifolia is here for the first time reported from Peru, bringing the species total for the county to 12. A second putative interspecific hybrid, Malesherbia ardens × M. arequipensis, is reported from Department Moquegua. This indicates that species of Malesherbia may hybridize when eco-geographical separation breaks down due to habitat modification. The new species and the two novel hybrids are described and illustrated.